2021
DOI: 10.3390/ijms222011013
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated and Carboxymethylated β-Glucan Derivatives with Inhibitory Activity against Herpes and Dengue Viruses

Abstract: The infection of mammalian cells by enveloped viruses is triggered by the interaction of viral envelope glycoproteins with the glycosaminoglycan, heparan sulfate. By mimicking this carbohydrate, some anionic polysaccharides can block this interaction and inhibit viral entry and infection. As heparan sulfate carries both carboxyl and sulfate groups, this work focused on the derivatization of a (1→3)(1→6)-β-D-glucan, botryosphaeran, with these negatively-charged groups in an attempt to improve its antiviral acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…A modest effect at living viral levels was noted at 24 hours post-infection in this study. Similarly, the antiviral activity of β-glucan inhibiting the pathogens on macrophages has been demonstrated for influenza A virus, mycobacteria, tuberculosis, and herpes simplex virus 1 and indicated that β-glucan significantly decreased the pathogen growth and induced the cytokines expression through activating the JAK-STAT and TLR signaling pathways, especially produce type I IFN genes ( Harada et al ., 2006 ; Wang et al ., 2019 ; Moorlag et al ., 2020 ; Lopes et al ., 2021 ; Perveen et al ., 2021 ; Krishnan et al ., 2022 ; Pan et al ., 2022 ). The findings from our study have shown that β-glucan protected the host against the ASFV invasion in PAMs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A modest effect at living viral levels was noted at 24 hours post-infection in this study. Similarly, the antiviral activity of β-glucan inhibiting the pathogens on macrophages has been demonstrated for influenza A virus, mycobacteria, tuberculosis, and herpes simplex virus 1 and indicated that β-glucan significantly decreased the pathogen growth and induced the cytokines expression through activating the JAK-STAT and TLR signaling pathways, especially produce type I IFN genes ( Harada et al ., 2006 ; Wang et al ., 2019 ; Moorlag et al ., 2020 ; Lopes et al ., 2021 ; Perveen et al ., 2021 ; Krishnan et al ., 2022 ; Pan et al ., 2022 ). The findings from our study have shown that β-glucan protected the host against the ASFV invasion in PAMs.…”
Section: Resultsmentioning
confidence: 99%
“…IL-6 is a regulatory cytokine that activates natural killer, T helper 1 (Th1), and Th17 cells to produce IFN and reduce apoptosis and cytolysis ( Ikeda et al ., 2007 ). Therefore, IFNs plays an important role in activating the process of phagocytosis and improving protection against intracellular viral infections ( Mochizuki et al ., 2013 ; Udayangani et al ., 2017 ; Dos Santos et al ., 2019 ; Wang et al ., 2019 ; Liu et al ., 2021 ; Lopes et al ., 2021 ; Pan et al ., 2022 ). A recent study showed that ASFV infection at the doses of 1 and 0.1 MOI for 24 hours significantly increased IFNα production in PAMs when compared to control in PAMs ( Li et al ., 2021 ; Wang et al ., 2021 ), suggesting the protective role of type I IFN in response to ASFV infection.…”
Section: Resultsmentioning
confidence: 99%
“…СПС предлагают многообещающую терапию -альтернативу про-тивовирусным синтетическим препаратам для терапии больных. Они ингибируют первую стадию инфекции клеток оболочечными вирусами, при этом гликопротеин вирусной оболочки использует свои положительные заряды для взаимодействия с отрицательными зарядами гепарансульфата (HS), с которым связывается вирус, т. е. СПС имитируют HS, блокируя проникновение возбудителя в клетку-хозяина [84].…”
Section: действие биологически активных веществ водорослей на вирусы-...unclassified
“…They inhibit the first step of infection, where the glycoprotein on the viral envelope utilizes its positive charges to interact with negative charges of heparan sulfate (HS), one of the host cell surface receptors. By inhibiting this step, polysaccharides mimic HS, thus blocking the virus from entering the host cell [41,42].…”
Section: Antiviral Activitymentioning
confidence: 99%
“…LLaEPS-C (0.7 mg/ml) was the only fraction that showed anti-hRSV activity statistically significant, demonstrating that the carboxymethylation improved the antiviral activity from LLaEPS. [42] (LOPES et al, 2021a). They suggest introducing carboxymethyl groups may change the triple-helix conformation of polysaccharides [2].…”
Section: Antiviral Activitymentioning
confidence: 99%